ANALISIS ETIKA PESERTA DIDIK DALAM PROSES BELAJAR MENGAJAR DI KELAS VIII E SMP NEGERI 18 PONTIANAK - Elda Safitri; Aminuyati Aminuyati; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the Analysis of Students' Ethics in the Teaching and Learning Process of class VIII E at SMP Negeri 18 Pontianak seen from the aspect of the ethical form of students, the process of implementing student ethics, and supporting factors that inhibit students' ethics. The research method used is descriptive qualitative. This research was conducted at SMP Negeri 18 Pontianak in class VIII E, totaling 32 students. Data collection techniques used are observation, interviews, and documentation. Based on the results of the data analysis that the researchers conducted, it was concluded that in terms of the form of student ethics, the process of implementing student ethics, and supporting factors that inhibited student ethics were categorized as very good. The Ethics of Class VIII E Students in the Teaching and Learning Process has been carried out well and according to the rules given by the Social Science subject teacher, namely students prepare and pray before the teaching and learning process begins, students are disciplined in time, students focus on following the teaching and learning process, students work on and collect assignments given by the teacher, and students have a sense of respect for teachers and friends.